2022
DOI: 10.23960/jat.v10i1.5253
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH BERBAGAI JENIS AUKSIN DENGAN BEBERAPA KONSENTRASI TERHADAP PENGAKARAN SETEK MELADA (Piper colubrinum)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh berbagai jenis auksin terhadap beberapa konsentrasi terhadap pengakaran Piper colubrinum. Percobaan dilaksanakan di Rumah Kaca  Fakultas Pertanian Universitas Lampung dari bulan Mei 2018 sampai Desember 2018. Percobaan menggunakan rancangan acak lengkap dengan 3 ulangan. perlakuan yang mengaplikasikan: kontrol, IBA 1500 ppm, IBA 2000 ppm, NAA 2000 ppm, NAA 750 ppm + IBA 750 ppm, NAA 1000 ppm + IBA 1000 ppm. Hasil penelitian menunjukkan bahwa pada variabel juml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…When we compare the effect of NAA with IBA+NAA, it is interesting to note that the mixture of the two auxins at 2000 ppm resulted in higher root growth than NAA alone as indicated by higher root length and root fresh weight. This fenomenon was also reported by Prajapati et al (2018) on cuttings of Piper nigrum; Yusnita et al (2018) on cuttings of Malay apple, and in our previous study using P. colubrinum cuttings (Hanum et al, 2022). In the shoot growth parameters (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When we compare the effect of NAA with IBA+NAA, it is interesting to note that the mixture of the two auxins at 2000 ppm resulted in higher root growth than NAA alone as indicated by higher root length and root fresh weight. This fenomenon was also reported by Prajapati et al (2018) on cuttings of Piper nigrum; Yusnita et al (2018) on cuttings of Malay apple, and in our previous study using P. colubrinum cuttings (Hanum et al, 2022). In the shoot growth parameters (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Greater effects of IBA and NAA combination than single IBA for rooting of cuttings was also demonstrated in other species such as Malay apple (Yusnita et al, 2018). In our previous experiment with P. colubrinum cuttings, it was found that a combination of IBA and NAA stimulated higher number of primary adventitious roots than those treated with IBA or single NAA (Hanum et al, 2022). However, the total auxin concentrations tested were only 1500 and 2000 ppm, and the number of roots produced were still in trend of increment.…”
Section: Introductionmentioning
confidence: 63%